Influencing factors of customer satisfaction and purchase decision in Apple products: English - Fellicia, Nadilla; Berlianto, Margaretha Pink (Enrichment : Journal of Management, 2024)
This study analyzes the influence of Corporate Social Responsibility, Social Media Marketing (SMM), Store Environment, Sales Promotion, and Perceived Value on purchasing decisions for Apple products.”The path analysis method with the PLS-SEM approach was used on 265 respondents, with data collected through an online questionnaire with a Likert scale of 5. The results show that Corporate Social Responsibility, Social Media Marketing, Store Environment, and Satisfaction significantly affect purchasing decisions. Satisfaction with Trust also has a significant effect. Meanwhile, Perceived Value and Sales Promotion don’t substantially affect Purchase Decisions. The practical implication is that companies must strengthen Corporate Social Responsibility, Social Media Marketing, and shopping experiences and evaluate promotional strategies to influence purchasing decisions more effectively. Companies should strengthen Corporate Social Responsibility initiatives, enhance social media marketing strategies, and improve the store environment to impact customer satisfaction and purchasing decisions. Promotional strategy should be carefully evaluated, as Sales Promotion alone does not significantly affect purchase behavior. This research gives insightful ideas for brand managers aiming to enhance marketing strategies, maintain customer engagement, and sustain a competitive advantage